Effect of Removing Contact Precautions for Multidrug-Resistant Organisms on Hospital Infections in a Pediatric Health System. (October 2020) - Linam, Matthew; Hoskins, Dorian; Jaggi, Preeti; Gonzalez, Mark; Watson, Renee; Shane, Andi
Abstract : Background: Discontinuation of contact precautions for methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococci (VRE) have failed to show an increase in associated transmission or infections in adult healthcare settings. Pediatric experience is limited. Objective: We evaluated the impact of discontinuing contact precautions for MRSA, VRE, and extended-spectrum β-lactamase–producing gram-negative bacilli (ESBLs) on device-associated healthcare-associated infections (HAIs). Methods: In October 2018, contact precautions were discontinued for children with MRSA, VRE, and ESBLs in a large, tertiary-care pediatric healthcare system comprising 2 hospitals and 620 beds. Coincident interventions that potentially reduced HAIs included blood culture diagnostic stewardship (June 2018), a hand hygiene education initiative (July 2018), a handshake antibiotic stewardship program (December 2018) and multidisciplinary infection prevention rounding in the intensive care units (November 2018). Compliance with hand hygiene and HAI prevention bundles were monitored. Device-associated HAIs were identified using standard definitions. Annotated run charts were used to track the impact of interventions on changes in device-associated HAIs over time. Results: Average hand hygiene compliance was 91%. Compliance with HAI prevention bundles was 81% for ventilator-associated pneumonias, 90% for catheter-associated urinary tract infections, and 97% for central-line–associated bloodstream infections. Overall, device-associated HAIs decreased from 6.04 per 10, 000 patient days to 3.25 per 10, 000 patient days after October 2018 (Fig. 1). Prior to October 2018, MRSA, VRE and ESBLs accounted for 10% of device-associated HAIs. This rate decreased to 5% after October 2018. The decrease in HAIs was likely related to interventions such as infection prevention rounds and handshake stewardship. Conclusions: Discontinuation of contact precautions for children with MRSA, VRE, and ESBLs were not associated with increased device-associated HAIs, and such discontinuation is likely safe in the setting of robust infection prevention and antibiotic stewardship programs. Funding: None Disclosures: None